Drought and depression - Marchildon, Gregory P., 1956- (History of the Prairie West series, 2018)
"The Great Depression of the 1930s often recalls images of the drought-stricken Great Plains. Prolonged drought exacerbated the economic effects of the Great Depression to such a degree that the prairies became the epicentre of the disaster in Canada. Between 1929 and 1932, per capita incomes fell by 49% in Manitoba, 61% in Alberta and an astounding 72% in Saskatchewan. The result was enormous social and political upheaval that sent shockwaves through the rest of the country. In this sixth volume of the History of the Prairie West series, contributors explore the cultural, political, and economic repercussions of climate change and financial upheaval on the region and its people."--